95.8k views
1 vote
Factor the expression 6p^3-12p^2+9p

1 Answer

3 votes

Answer:


3p(2p^2-4p+3)

Explanation:

Given polynomial:


6p^3-12p^2+9p

To factor out the polynomial completely.

Solution:

Factoring the given polynomial by first factoring the GCF.

The GCF can be found by listing the factors of each term.


6p^3=2* 3* p* p* p


-12p^2=-1* 2* 2* 3* p* p


9p=3* 3* p

Thus , the GCF of the terms is =
3p

Factoring
3p from each term.


3p(2p^2-4p+3) (Answer)

The above expression cannot be factored any further.

User LB Ben Johnston
by
5.3k points